Exact chirped solutions, stability analysis, chaotic behaviors and dynamical properties of the nonlinear Schrödinger equation with anti-cubic law nonlinearity - Zhang, Bingwen (Revista Mexicana de Física, 2025)
In this paper, the dynamical properties of the nonlinear Schrödinger equation with anti-cubic law nonlinearity is studied. By using the trial equation method and the complete discrimination system for polynomial method, the exact chirped solutions of the equation are obtained, and the parametric stability of these modes is analyzed. Finally, we study the chaotic behaviors of the equation with perturbation terms.